Changes in the Fetal and Neonatal Cytokine Profile in Pregnancies Complicated by Fetal Growth Restriction. (24th December 2012) - Mullins, Edward; Prior, Tomas; Roberts, Irene; Kumar, Sailesh
<x xml:space="preserve">Abstract</x> Fetal growth restriction (FGR) is a major complication of pregnancy with unknown etiology which results in marked fetal, neonatal and long‐term morbidity, and mortality. FGR is likely to result from suboptimal placental implantation and perturbed immunological interactions. The diagnostic criteria for FGR vary between studies and the condition often occurs with pre‐eclampsia. Here, we review published studies of fetal and neonatal cytokines in FGR and compare these with studies of small for gestational age, pre‐eclampsia and pregnancies delivering pre‐term.